Nasopharyngeal density of respiratory viruses in childhood pneumonia in a highly vaccinated setting: findings from a case–control study - Andrew Martin; Peter Richmond; Adam Jaffe; Mejbah Uddin Bhuiyan; Jurissa Lang; Chisha Sikazwe; Meredith Borland; David Smith; Tom Snelling; Christopher Blyth (BMJ Open Respiratory Research)
Background Detection of pneumonia-causing respiratory viruses in the nasopharynx of asymptomatic children has made their actual contribution to pneumonia unclear. We compared nasopharyngeal viral density between children with and without pneumonia to understand if viral density could be used to diagnose pneumonia.Methods Nasopharyngeal swabs (NPS) were collected from hospitalised pneumonia cases at Princess Margaret Hospital (PMH) and contemporaneous age-matched controls at PMH outpatient clinics and a local immunisation clinic in Perth, Australia. The density (copies/mL) of respiratory syncytial virus (RSV), influenza A virus (InfA), human metapneumovirus (HMPV) and rhinovirus in NPS was determined using quantitative PCR. Linear regression analysis was done to assess the trend between viral density and age in months. The association between viral density and disease status was examined using logistic regression. Area under receiver operating characteristic (AUROC) curves were assessed to determine optimal discriminatory viral density cut-offs.Results Through May 2015 to October 2017, 230 pneumonia cases and 230 controls were enrolled. Median nasopharyngeal density for any respiratory virus was not substantially higher in cases than controls (p>0.05 for each). A decreasing density trend with increasing age was observed—the trend was statistically significant for RSV (regression coefficient −0.04, p=0.004) but not for other viruses. After adjusting for demographics and other viral densities, for every log10 copies/mL density increase, the odds of being a case increased by six times for RSV, three times for HMPV and two times for InfA. The AUROC curves were <0.70 for each virus, suggesting poor case–control discrimination based on viral density.Conclusion The nasopharyngeal density of respiratory viruses was not significantly higher in children with pneumonia than those without; however, the odds of being a case increased with increased density for some viruses. The utility of viral density, alone, in defining pneumonia was limited.